Caught between Paper Plans and Kashmir Politics: Disaster Governance in Ladakh, India - Field, Jessica (2020)
Disaster governance encompasses the responsibility and management of disaster mitigation, relief and recovery as well as power and politics around these areas of action. Research on disaster governance focuses on various scales of action when examining the implications of disaster governance frameworks for particular populations and there is growing scholarship on the impacts that national politics and programmes have on local efforts. Under-represented in these discussions is an engagement with the relationality of disaster governance within national boundaries, not just vertically (i.e., the local in relation to the national) but horizontally—the local in relation to other locals. Through an examination of Ladakh in relation to neighbouring Kashmir, this article shows how local efforts to enhance disaster governance have been stymied both by the vertical (local-centre) politics of border security and conflict, as well as by the material effects that politics and violence in neighbouring Kashmir Valley have on Ladakh.